THE FILM 'PESANTREN' AND RELIGIOUS TOLERANCE IN INDONESIA: REALITY, REPRESENTATION AND IDEOLOGY - Abdullah, Irfan Mas’ud; Hasbi, Rusli; Fatihunnada, Fatihunnada; Ummah, Sayidatul (UIN Raden Mas Said Surakarta, 2023)
This article aims to explain the form of religious tolerance values in the documentary film 'Pesantren' which was released in 2022. This film is interesting because it reveals the educational side of religious tolerance in Indonesia, which shows another side of pesantren, which is considered by some to be a hotbed of indoctrination of radical and fundamental religious views. Through descriptive qualitative method, this article focuses on the value of religious tolerance in the film presented through verbal and non-verbal signs. The data is analyzed using John Fiske's semiotic theory that explains the codes of television, namely the level of reality, the level of representation and the level of ideology. This theory is useful to reveal the meaning behind each scene. This article shows that in the film Pesantren, the value of tolerance is more dominant after reading the ideology stage. The value of tolerance in the film is present in the frame of inter and intra-religious tolerance. The value is instilled in three major narratives, namely: respecting differences of opinion, avoiding fanaticism because God's love is also unlimited, preaching with good words and staying away from discrimination against people of different beliefs.